2021
DOI: 10.1177/2325967121992375
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Head Contacts, Penalties, and Player Contact Behaviors in Youth Ice Hockey: Evaluating the “Zero Tolerance for Head Contact” Policy Change

Abstract: Background: To reduce the risk of concussion in youth ice hockey, Hockey Canada implemented a national “zero tolerance for head contact” (HC) policy in 2011. A previous cohort study revealed higher concussion rates after this implementation in players aged 11 to 14 years. However, it is unknown whether the elevated risk was due to higher HC rates or factors such as increased concussion awareness and reporting. Purpose: To compare the rates of primary and secondary HCs and HC policy enforcement in elite U15 ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The HC 1 and HC 2 rates observed in ringette are higher than previously reported in male U15 ice hockey. 21 Given these alarmingly high HC rates, our findings further support the need for additional research in this population to target the prevention of HCs in ringette and female ice hockey.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The HC 1 and HC 2 rates observed in ringette are higher than previously reported in male U15 ice hockey. 21 Given these alarmingly high HC rates, our findings further support the need for additional research in this population to target the prevention of HCs in ringette and female ice hockey.…”
Section: Discussionsupporting
confidence: 56%
“…This aligns with the literature that suggests many contacts in ringette and male ice hockey are deliberate in nature. 4,21 Given that many contacts are deliberate, this finding suggests that perhaps prevention strategies targeting better enforcement of rules are necessary in both ringette and female ice hockey.…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous research by Krolikowski et al 19 and Williamson et al, 15 this study aimed to investigate additional rule modifications regarding the national "zero tolerance for HC" policy in U15 Canadian youth ice hockey. Previously with the implementation of the HC policy, increased rates of concussion (presumably because of increased concussion awareness and reporting over the study period) were found.…”
Section: Discussionmentioning
confidence: 99%
“…15 In both cohorts, less than 14% of direct player-inflicted HC (HC1s) were penalized during play. 15 Potentially stricter enforcement or rule modifications were needed to increase player safety. Hockey Canada's 2018 to 2020 rule amendments have not been previously evaluated in youth ice hockey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation